Costs and Operational Performance of Eucalyptus Wood Extraction Using Aerial Cable - Simöes, Danilo [UNESP]; Fenner, Paulo Torres [UNESP]; Bantel, Carlos Adolfo [UNESP] (FapUNIFESP (SciELO), 2010)
This study aimed to technically and economically evaluate the aerial cable in the extraction of eucalyptus wood in mountainous region. The technical analysis comprised a study of time and movements by continuous method and productivity was determined by the volume in cubic meters of wood extracted. Economical analysis comprised operational costs parameters and wood extraction cost. Results referred to effective operational performance. The average cost of extraction of wood was US$ 3.35 per cubic meter with operating performance per effective hour of work of 14.16 m3 h-1.
Custos erendmentos operacionais da extração de madeira de eucalipto com cabo aéreo
Keywords: Production costs; Timber harvesting; Times and movement